PRE-EMPTIVE EFFECT OF INTRAVENOUS PARACETAMOL VERSUS INTRAVENOUS KETOROLAC ON POST-OPERATIVE PAIN AND SHIVERING AFTER SEPTOPLASTY UNDER GENERAL ANESTHESIA: A COMPARATIVE STUDY - Kashif, Sanum; Kundi, M Nasir; Khan, Taimur Azam (Pakistan Armed Forces Medical Journal, 2021)
Objective: To observe the pre-emptive effect of intravenous paracetamol versus intravenous ketorolac in preventing postoperative shivering and pain after septoplasty in postoperative care unit. Study Design: Prospective comparative study. Place and Duration of Study: Main Operation Theatre of Frontier Corps Hospital Quetta, from Sep to Dec 2019. Methodology: After ethical committee approval, 90 American Society of Anaesthesiologist (ASA-I patients, aged between 18-45 years, scheduled for septoplasty, were recruited and divided into three equal groups, Paracetamol (PA), Ketorolac (KE) and Placebo (PL) as per computer generated table. The paracetamol (PA) group (n=30) received 1gm intravenous paracetamol, ketorolac (KE) group (n=30) received 30mg intravenous ketorolac and group placebo (PL) received 100ml normal saline, 20 minutes before completion of surgery. Postoperative shivering and pain was assessed via four-point scale and visual analogue scale (VAS) respectively, in post-anesthesia care unit at 10 and 30 minutes post-extubation. Results: Mean visual analog scale (VAS) score in paracetamol group was 2.7 ± 1.41, ketorolac group was 2.3 ± 1.24 and in placebo group was 3.6 ± 1.44, with a p-value of 0.002. Mean four point shivering score in paracetamol group was 0.3 ± 0.55, ketorolac was 0.7 ± 0.78 and placebo group was 1.4 ± 1.00, with a p-value of <0.001. Conclusion: The effect of paracetamol is better than ketorolac in preventing pain and shivering after septoplasty under general anesthesia.